Energy policy in Iran domestic choices and international implications - Mossavar-Rahmani, Bijan (Pergamon Press, 1981)
Energy Policy in Iran: Domestic Choices and International Implications presents the assessment of energy demand patterns; evaluation of major energy supply; and recommendation of policies and guidelines for an integrated energy plan for Iran. This text is comprised of 11 chapters; the opening chapter discusses Iran in an international setting. Chapter 2 covers the economic framework for long-range policy, while Chapter 3 discusses the historical pattern. The fourth chapter discusses energy demand projections and the succeeding chapter covers energy sources and strategies, such as oil, natural gas, hydropower, solid and miscellaneous fuels, electricity, and nuclear power. The last chapter covers petrochemicals. This book will be of great interest to readers who are concerned with Iran's energy policies and its implications.--Provided by publisher.